1998
DOI: 10.1016/s0014-5793(98)00613-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, tissue distribution and androgen regulation of rat protein C inhibitor

Abstract: Protein C inhibitor (PCI) is the plasma serine protease inhibitor of activated protein C, the active enzyme of the anticoagulant protein C pathway. Recently, PCI was also detected in human seminal plasma and reproductive organs (testis, seminal vesicle and prostate) suggesting that PCI may also play an important role in the reproductive system. In this study, we cloned the full length of rat PCI cDNA, and determined its amino acid sequence and tissue distribution. We also evaluated the effect of androgen on PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 37 publications
(39 reference statements)
4
34
0
Order By: Relevance
“…In rodents, PCI is expressed only in reproductive organs; unlike humans, PCI is absent in the liver and kidneys and the blood level of PCI is undetectable in rats and mice [23,24]. We have previously developed and characterized human PCI transgenic mice that express high levels of human PCI in several organs including the liver, kidneys and the lungs.…”
Section: Resultsmentioning
confidence: 99%
“…In rodents, PCI is expressed only in reproductive organs; unlike humans, PCI is absent in the liver and kidneys and the blood level of PCI is undetectable in rats and mice [23,24]. We have previously developed and characterized human PCI transgenic mice that express high levels of human PCI in several organs including the liver, kidneys and the lungs.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the reduced sperm count and testicular alterations in hsf2-deficient mice may be a consequence of inhibition of spermatozoa division and survival due to reduced levels of meg 1. Several genes with enhanced expression levels in the testes of hsf2-deficient mice, such as angiotensinogen, plasminogen activator, plasminogen activator inhibitor 3, transketolase, and kallikrein 5, were also of particular interest due to their roles in testicular cell development and function (Datta et al, 1987;Saitoh et al, 1987;Tempfer et al, 2000;Uhrin et al, 2000;Wakita et al, 1998). For example, high levels of the serine protease kallikrein 5 have been associated with azoospermia in humans (Saitoh, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, PCI mRNA is expressed in many tissues, including liver, kidney, pancreas, skin, and the male and female reproductive organs (Geiger 2007; Krebs et al 1999) while PCI protein was additionally found in different body fluids, including plasma, urine, synovial fluid, sweat, tears, milk, seminal plasma, Graaf follicle fluid, and cerebrospinal fluid (Laurell et al 1992). In rodents, PCI is predominantly expressed in the male and female reproductive organs (Uhrin et al 2000; Wagenaar et al 2000; Wakita et al 1998). In humans, the functional role in vivo was tested in venous thrombosis, where elevated levels of PCI constituted a mild risk factor for thrombosis (Meijers et al 2002) indicating that of the possible actions of PCI: anticoagulant by inhibition of coagulation enzymes, anti-antifibrinolytic by inhibition of the thrombin activatable fibrinolysis inhibitor (TAFI) activation by thrombin-thrombomodulin, anti-anticoagulant by inhibition of activated protein C and protein C activation by thrombomodulin, and antifibrinolytic by the inhibition of urokinase, the last two options predominate in vivo.…”
Section: Introductionmentioning
confidence: 99%